Modulation of influenza vaccine immune responses using an epidermal growth factor receptor kinase inhibitor - Pulit-Penaloza, Joanna A. (Sci Rep, 2015)
Systemic use of epidermal growth factor receptor inhibitors (EGFRIs) has been shown to alter MHC expression and that of several chemokines, and to enhance immune cell recruitment into human skin. We hypothesized that EGFRIs may have value as cutaneous immune response modifiers, and determined the effects of topical application of an irreversible EGFRI on a well-established murine model of influenza vaccination. We found that a single topical application of an EGFRI led to increased levels of antibodies that inhibit influenza mediated hemagglutination and viral cytopathic effects. The topically applied EGFRI significantly enhanced the generation of vaccine-specific IL-4 and IFN-γ producing cells within skin-draining lymph nodes as early as one week following vaccination. The EGFRI/vaccine group showed a twelve-fold reduction in detectable pulmonary viral load four days after infection as compared to the vaccine alone control group. The reduction in the lung viral titers correlated with the survival rate, which demonstrated 100% protection in the EGFRI/vaccine immunized group but only 65% protection in the mice immunized with vaccine alone. These findings are significant because they demonstrate that inhibition of defined signaling pathways within the skin using small molecule kinase inhibitors provides a novel approach to enhance immune responses to vaccines.